APLIKASI GEOMETRI FRAKTAL DAN TRANSFORMASI LINIER BIDANG DALAM PENGEMBANGAN MOTIF BATIK BESUREK - MAYASARI, ZULFIA MEMI; AFANDI, NUR; RAFFLESIA, ULFASARI (E-Jurnal Matematika; Vol 13 No 2 (2024), 2024)
Batik besurek is a typical batik from Bengkulu Province. B atik b esurek has a unique and strong character, in the form of a rabic calligraphy. This study aims to develop the pattern of batik besurek motif by applying the fractal principle and linear transformation of fields in order to enrich the style and culture of  Bengkulu Province a nd can add to selling value . The pattern development is done by determining the pattern of batik besurek which will be developed , later using mathematical principles through the fractal principle and linear transformation of field s will be made a new pattern of batik besurek motif. The results of this study is a new beautiful batik besurek motif obtained from the development of original motif which can add to the richness of the batik besurek motif. This motif keeps the original motif and the symbols in it.